Analisis Yuridis Penyelesaian Perkara Gugatan Murabahah Di Pengadilan Agama Kota Kediri (Studi Putusan Tingkat Pertama No.0176/Pdt.G/2020/Pa.Kdr Dan Putusan Banding No.487/Pdt.G/2020/Pta.Sby) - Eliana Lailatul Khofifa; Trinah Asi Islami (Universitas Merdeka Madiun, 2022)
This study intends to examine problems related to the Ratio of Judges at the First Level Court of the Religious Courts of Kediri City with the Appellate Panel of Judges in the Murabahah Lawsuit case based on Decision No.0176/Pdt.G/2020/PA.Kdr and the Decision No.487/Pdt.G/2020/PTA.Sby and to find out the legal remedies for the settlement of the Murabahah lawsuit N.0176/Pdt.G/2020/PA.Kdr in creating legal goals for the plaintiff. In writing this study using library research because it uses library materials as the main data source. The results of the study show that the decision of the case No.0176/Pdt.G/2020/PA.Kdr determined the Religious Court of the City of Kediri that it did not adjudicate the case of accounts receivable, the decision of the case No.487/Pdt.G/2020/PTA.Sby the lawsuit filed could not accepted on the grounds of the decision of the panel of judges at the appellate level stating that the lawsuit filed contains a formal defect or lawsuit or is premature and obscuur libel. So in this case to create a legal goal for the plaintiffs, namely by filing the Aquo case in the District Court.